2004
DOI: 10.1104/pp.104.039511
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Inhibitor of 9-cis-Epoxycarotenoid Dioxygenase in Abscisic Acid Biosynthesis in Higher Plants

Abstract: Abscisic acid (ABA) is a major regulator in the adaptation of plants to environmental stresses, plant growth, and development. In higher plants, the ABA biosynthesis pathway involves the oxidative cleavage of 9-cis-epoxycarotenoids, which may be the key regulatory step in the pathway catalyzed by 9-cis-epoxycarotenoid dioxygenase (NCED). We developed a new inhibitor of ABA biosynthesis targeting NCED and named it abamine (ABA biosynthesis inhibitor with an amine moiety). Abamine is a competitive inhibitor of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 52 publications
2
72
0
Order By: Relevance
“…This was associated morphogenetically with inhibited plumule apex growth and leaf primordium elongation ( Figures 3D and E), decreased number and length of axial and lateral buds and shorter length of compound leaves ( Figure 4D and E) during seed germination. Naproxen, the potent ABA biosynthesis inhibitor specifically targeting to NCED, is known to decrease endogenous ABA levels in higher plants (Han et al, 2004;Wan and Li, 2006). In the present study, we found that naproxen treatment decreased the levels of endogenous ABA ( Figure 2B) and AhNCED1 gene transcript ( Figure 2A) and concomitantly increased α-amylase activity ( Figure 2C), germination rate ( Figure 1C) and viability index ( Figure 1D) of germinating seeds.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This was associated morphogenetically with inhibited plumule apex growth and leaf primordium elongation ( Figures 3D and E), decreased number and length of axial and lateral buds and shorter length of compound leaves ( Figure 4D and E) during seed germination. Naproxen, the potent ABA biosynthesis inhibitor specifically targeting to NCED, is known to decrease endogenous ABA levels in higher plants (Han et al, 2004;Wan and Li, 2006). In the present study, we found that naproxen treatment decreased the levels of endogenous ABA ( Figure 2B) and AhNCED1 gene transcript ( Figure 2A) and concomitantly increased α-amylase activity ( Figure 2C), germination rate ( Figure 1C) and viability index ( Figure 1D) of germinating seeds.…”
Section: Discussionsupporting
confidence: 52%
“…The ABA-mediated inhibition of seed germination in peanut thus exhibited a dose-dependency ( Figures 1A and B). Naproxen, the potent ABA biosynthesis inhibitor specifically targeting to NCED (Han et al, 2004) increased the germination rate and viability index (Figures 1C and D). At day 2 and 6 after the onset of imbibition, the germination rate of germinating seeds treated with 0.5 mmol/l naproxen were respectively, 1.13 and 1.50 times as high as that of the control germinating seeds ( Figure 1C); accordingly, the viability index of seeds treated with 0.5 mmol/l naproxen was respectively, 1.35 and 1.92 times as much as that of control seeds ( Figure 1D).…”
Section: Effects Of Aba and Naproxen On Germination Rate And Viabilitmentioning
confidence: 99%
See 1 more Smart Citation
“…17) Abamine (ABM) is the first reported abscisic acid biosynthesis inhibitor that targets nine-cis-epoxycarotenoid dioxygenases (NCED), 12,13) and it has been suggested that abamine may also target other CCDs. 18) Interestingly, AbamineSG (ABMSG) was developed as an abscisic acid biosynthesis inhibitor based on the structural and functional characteristics of abamine, but was found to be a more specific and potent NCED inhibitor than abamine.…”
Section: Resultsmentioning
confidence: 99%
“…Abamine was synthesized using the method outlined by Han et al 12,13) GR24, a synthetic mimic of strigolactones, was synthesized as previously described. 14) In this study, GR24 with the same relative stereochemistry as (Ϯ)-strigol was used.…”
Section: Chemicalsmentioning
confidence: 99%